Pengembangan Skill Guru-Guru Di SMK PGRI Sooko Kabupaten Mojokerto Dengan Edukasi Desain Dan Pembuatan Bahan Ajar Berbasis Online Dan Offline - Elfia Nora; Imam Bukhori; I Nyoman Suputra (BADAN PENERBIT STIEPARI PRESS, 2023)
In this disruptive era, all organizations, institutions, or institutions need to make improvements, improvements, and developments in various aspects. Teachers are human resources driving the achievement of school goals and also the nation, namely educating students by transferring knowledge according to their fields of competence, with actions, presenting teaching materials using interesting and innovative media, delivered offline and online. Online teaching materials developed by teachers can be made from Google sites, genially, bookcerator, Visme applications, Sigil, flip PDF and others. While offline or print out teaching materials in the form of textbooks, from each subject that is adjusted to the basic competencies that have been formulated that must be combined or learned by students. According to the results of the presentation of the situation analysis and observations that have been made to the place of partners who are willing to cooperate in the implementation of community service, the problems of partners are formulated as follows: 1) There is still a lack of teachers developing teaching materials made by themselves, to be used for the learning process, 2) Teaching materials used by teachers to teach are still lacking both online and offline-based. To overcome partner problems, the methods that will be implemented in this community service activity are: 1) Providing education on various types of online and offline-based teaching materials. 2) Providing assistance and guidance, making online-based teaching materials, using the Google Sites application and genially and offline by providing innovations in teaching materials, and printed. The results of the delivery of education for making online and offline-based teaching materials are 1) Teachers have never used learning media using the Google Sites application, but are very enthusiastic about making teaching materials using this online media, 2) After being given education and assistance Teachers have immediately been able to make this online-based teaching materials, and the links to teaching materials that have been made, Try to share it with groups of students, for students to learn the material. Teachers should be given education or training on the application of making teaching materials or other interactive teaching media again.